2014
DOI: 10.7326/m14-0295
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Risk Communication

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
285
2
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(313 citation statements)
references
References 98 publications
5
285
2
11
Order By: Relevance
“…A core component of patient-centered communication processes is accurate information exchange about the diagnosis and risks and benefits of treatment options (29) that includes plain language, describes absolute instead of relative risks, and uses tables and graphs (30,31). In this study and our previous work, almost all patients reported not receiving adequate information about the risk of lung cancer, and most substantially overestimated this risk (17)(18)(19).…”
Section: Original Researchmentioning
confidence: 67%
“…A core component of patient-centered communication processes is accurate information exchange about the diagnosis and risks and benefits of treatment options (29) that includes plain language, describes absolute instead of relative risks, and uses tables and graphs (30,31). In this study and our previous work, almost all patients reported not receiving adequate information about the risk of lung cancer, and most substantially overestimated this risk (17)(18)(19).…”
Section: Original Researchmentioning
confidence: 67%
“…Studies about evidence-based risk communication have found that relative risk reductions are harder to understand and generate more unrealistic expectations compared to the same information presented as absolute risk reductions. 16,17 If the aim of communication is to assist women to understand the likelihood of a benefit, relative risks should be avoided in favour of absolute risks, and the harms should be presented in the same way using the same denominator, so that the chances of experiencing benefits and harms are directly comparable. 16 Women were often directly encouraged to attend, but were not given specific estimates of the benefit.…”
Section: Problems With Current Practicementioning
confidence: 99%
“…16,17 If the aim of communication is to assist women to understand the likelihood of a benefit, relative risks should be avoided in favour of absolute risks, and the harms should be presented in the same way using the same denominator, so that the chances of experiencing benefits and harms are directly comparable. 16 Women were often directly encouraged to attend, but were not given specific estimates of the benefit. For example one invitation letter says, 'The purpose is to reduce the number of cases and mortality from cervical cancer' (Norway), and an information leaflet says, 'Early detection and treatment of changes in the cells of the cervix can prevent cervical cancer' (Ireland).…”
Section: Problems With Current Practicementioning
confidence: 99%
“…In the 1980s and 1990s, the concept of danger was confined to the field of natural disasters and disaster management was meant to limit the extent of the consequences and the vulnerability to hazards [6]. However later on, the term "risk" was used in various areas such as natural disasters, human disasters (including; crime, health-related consequences, traffic accidents, air pollution and terror), different sciences (including insurance and economics, psychology and statistics) [5][6][7][8][9][10].…”
mentioning
confidence: 99%